Queen for a day : transformistas, beauty queens, and the performance of femininity in Venezuela - Ochoa, Marcia, 1970- (Perverse modernities., 2014)
Queen for a Day connects the logic of Venezuelan modernity with the production of a national femininity. In this ethnography, Marcia Ochoa considers how femininities are produced, performed, and consumed in the mass-media spectacles of international beauty pageants, on the runways of the Miss Venezuela contest, on the well-traveled Caracas avenue where transgender women (transformistas) project themselves into the urban imaginary, and on the bodies of both transformistas and beauty pageant contestants (misses). Placing transformistas and misses in the same analytic frame enables Ochoa to delv.